Time Value of Money dalam Perspektif Hukum Islam - Ilyas, Rahmat (al-'adalah, 2017)
This article reveals the Islamic view of the concept of Time Value of Money (referred by economists as positive time preference). This concept states that the value of commodities at present is higher than in the future. Time Value of Money is closely linked to the ‘discount’ concept that exists in capital and investment theory and, in practice, is used as a tool for project evaluation as well as investment decisions. This study concludes that Islam is not familiar with the concept of Time value of money. Islam only recognizes the concept of economic value of time. In Islamic view, money is simply a means of exchange, not a commodity. Similarly, the motive for money demand is to meet the needs of transaction, not for speculation.